Social Media Marketing and iPhone Repurchase Intention: The Roles of FOMO and Materialism - Fatimah Az Zahra; Ratna Roostika (Penerbit Goodwood, 2026)
Purpose: This study applies the stimulus–organism–response (S-O-R) framework to examine how Social Media Marketing Effectiveness (SMME) influences iPhone repurchase intention among Generation Z consumers in Indonesia, focusing on the mediating roles of Fear of Missing Out (FOMO), social comparison, and materialism. Methodology: Data were collected through an online questionnaire distributed to 285 Indonesian iPhone users who actively used social media. The proposed model was tested using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach via SmartPLS. Results: The findings indicate that SMME significantly enhances FOMO, whereas social comparison positively influences both FOMO and materialism. However, FOMO did not significantly affect repurchase intention. In contrast, materialism has a significant positive effect on repurchase intention, indicating that it represents a stronger and more stable psychological pathway for repeat purchasing behavior than FOMO. Conclusions: The results suggest that while social media marketing can activate short-term emotional responses such as FOMO, more enduring value orientations such as materialism play a more decisive role in shaping repurchase intentions for high-involvement symbolic products such as iPhones. Limitations: This study relied on cross-sectional, self-reported data from Indonesian consumers, which limits causal inference and generalizability to other product categories or cultural contexts. Contributions: This study extends the S-O-R framework by contrasting short-term affective and long-term value-based psychological mechanisms in explaining repurchase intention, offering both theoretical insights and practical guidance for social media marketing strategies.